STANDAR ISI, BAHASA, DAN PENYAJIAN BUKU TEMATIK TERBITAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN (2017) TEMA 2 “UDARA BERSIH BAGI KESEHATAN” KELAS V KURIKULUM 2013 - Halimatussa’diah Halimatussa’diah; Sudirman Sudirman; Heri Setiawan (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
Books are one of the learning resources as well as important teaching materials and are widely used in learning. Presentation of material in textbooks must meet predetermined standards. Currently, many writers are competing to publish textbooks without paying attention to the standards in writing and persentation of textbooks. Of course this can be a source of problems in learning. This study aims to determine the suitability of content, language, and presentation standards in the thematic monks published by the ministry of education and culture (2017) theme 2 class V curriculum 2013. The approach used in this study is a qualitative approach that specifiallt uses content analysis type research. Data collection techniques using documentary studies. Data analysis used interactive model data analysis from Miles & Huberman. The result showed that the suitability of thematic books published by the ministry of education and culture (2017) theme 2 class V curriculum 2013 seen from the content, language and presentation standards were obtaianed : 1) conformity to content standards was 93,05% or in very suitable category; 2) conformity to language standards was 93,32% or in very suitable category; 3) conformity to standards of presentation was 100% or in very suitable category.